HMB-45 Negative Adrenal Angiomyolipoma With A Synchronous Adrenal Adenoma – An Unusual Association - Nair, Gayathri G; Raju, Sreeja; Augustine, Joy; Nair, Vijayalakshmi (Annals of Pathology and Laboratory Medicine, 2020)
Background: Angiomyolipoma (AML) is an uncommon mesenchymal tumour usually found in the kidney. The most common extrarenal site is usually the liver. We report a case of adrenal AML with a predominant vascular component co-existing with an adrenal adenoma. Case report: A fifty-year-old male presented with two months history of dysuria. Computed tomography showed a heterogeneous lesion involving the right adrenal gland abutting the right kidney and adjacent liver capsule. Urine noradrenaline levels were elevated. Adrenalectomy specimen showed an encapsulated mass measuring 8 x 5 x3.5 cm with a lobulated, grey to tan brown cut surface with areas of haemorrhage and tiny cystic spaces. Another yellowish nodule measuring 1.3 x 1.2 x 1 cm was also noted at one pole. Microscopy showed a neoplasm composed predominantly thick-walled vascular channels admixed with foci of smooth muscle bundles and adipocytes. Yellowish nodule showed features of adrenal adenoma. HMB-45 was negative and CD34 positivity highlighted the thick and thin walled vessels. Conclusion: We present the very first case of HMB-45 negative adrenal AML with a predominant vascular component and a synchronous adrenal adenoma.